Plasma Neurofilament Light Chain as a Predictive Biomarker for Post-stroke Cognitive Impairment: A Prospective Cohort Study - Wang, Zhiqiang; Wang, Rongyu; Li, Yuxia; Li, Mao; Zhang, Yaodan; Jiang, Lianyan; Fan, Jin; Wang, Qingsong; Yang, Dongdong (Frontiers in Aging Neuroscience, 2021)
Background: Plasma neurofilaments light chain (pNfL) is a marker of axonal injury. The purpose of this study was to examine the role of pNfL as a predictive biomarker for post-stroke cognitive impairment (PSCI). Methods: A prospective single-center observational cohort study was conducted at the General Hospital of Western Theater Command between July 1, 2017 and December 31, 2019. Consecutive patients ≥18 years with first-ever acute ischemic stroke (AIS) of anterior circulation within 24 hours of symptom onset were included. PSCI was defined by the Montreal Cognitive Assessment (MOCA) (MOCA <26) at 90 days after stroke onset. Results: A total of 1,694 patients (male, 893 (52.70%); median age, 64 (16) years) were enrolled in the cohort analysis, and 1029 (60.70%) were diagnosed with PSCI. Patients with PSCI had significantly higher pNfL (median (IQR), 55.96 (36.13) versus 35.73 (17.57) pg/ml; P<0.001) than Non-PSCI. pNfL was valuable for the prediction of PSCI (OR 1.044, 95% CI 1.038–1.049, P<0.001) after a logistic regression analysis, even after adjusting for conventional risk factors including age, sex, education level, NIHSS, TOAST classification and infarction volume (OR 1.041, 95% CI 1.034–1.047, P<0.001). The optimal cutoff value of the pNfL concentration was 46.12 pg/ml, which yielded a sensitivity of 71.0% and a specificity of 81.5%, with the area under the curve (AUC) at 0.785 (95% CI 0.762 to 0.808, P<0.001). Conclusions: This prospective cohort study showed that the pNfL concentration within 48 hours of onset was an independent risk factor for PSCI 90 days after an anterior circulation stroke, even after being adjusted for potential influencing factors regarded as clinically relevant.